STRATEGI PERGURUAN TINGGI DALAM MENJAGA SUSTAINABILITY LEMBAGA MELALUI PROGRAM KEMITRAAN - Hasan Baharun; Niken Septantiningtyas; Iin Zainab (MANAGERE : Indonesian Journal of Educational Management, 2020)
This study aims to understand and analyze the application of the partnership program as a strategy for higher education in maintaining sustainability at Nurul Jadid Paiton University, Probolinggo. This research uses a qualitative approach with case study. The results showed that Nurul Jadid University carried out a partnership program with other agencies as a strategy in maintaining sustainability in the institution which was carried out through four stages, namely: Attention, namely creating awareness of the process and innovation in the institution; Interest, which is to raise interest from the community; Desire to choose an institution; Action, namely community action that makes the institution selected as its main choice. Through this community choice, the institution can maintain the sustainability of higher education. This research has implications for the importance of educational institutions in maintaining sustainability through their partner institutions, thus impacting public trust and public loyalty.